2014
DOI: 10.1186/1471-2091-15-11
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and subcellular localization of Drosophila organic solute carrier partner 1

Abstract: BackgroundOrganic solute carrier partner 1 (OSCP1) is known to facilitate the transport of various organic solutes into cells and reported to play a role in cell growth and cell differentiation. Moreover, OSCP1 is known as a tumor suppressor gene that is frequently down-expressed in nasopharyngeal carcinomas and acute myeloid leukemia. However, the underlying mechanisms of action remain unclear and the subcellular localization of OSCP1 has yet to be determined in detail.ResultsDrosophila contains a single orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Huu NT et al. found that dNOR1/dOSCP1 localizes in endoplasmic reticulum (ER) in salivary gland cells31. Interestingly, overexpression of dNOR1/dOSCP1 caused ER stress in Drosophila salivary gland cells, as evidenced by increase of ER chaperones marker KDEL immunostaining 26.…”
Section: Role Of Nor1 In Cancer Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Huu NT et al. found that dNOR1/dOSCP1 localizes in endoplasmic reticulum (ER) in salivary gland cells31. Interestingly, overexpression of dNOR1/dOSCP1 caused ER stress in Drosophila salivary gland cells, as evidenced by increase of ER chaperones marker KDEL immunostaining 26.…”
Section: Role Of Nor1 In Cancer Developmentmentioning
confidence: 99%
“…At present, except for human NOR1 gene, mouse, rat and Drosophila orthologue of NOR1 was successively isolated and well characterized29-31 (Figure 1A) (Table 1). Among these orthologues, mouse NOR1 (mNOR1) and Drosophila NOR1 (dNOR1) share 86% and 58% homology with its human counterpart, respectively 17, 31. Human NOR1/OSCP1 gene consists of 11 exons which is mapped to chromosome 1p34.2 and spans 33.4 kb of the genomic DNA.…”
Section: Gene Structure Evolution and Alternative Splicing Of Nor1mentioning
confidence: 99%
See 2 more Smart Citations
“…Although possible roles of OSCP1 have been reported using mammalian cell lines, only limited information is available regarding the function of OSCP1 in living organisms. In previous studies, we reported that Drosophila contains a single ortholog of OSCP1/NOR1 named dOSCP1 (CG13178) that shares 58% homology with its human counterpart . In the present study, we utilized the Drosophila melanogaster model for functional analysis of dOSCP1.…”
Section: Introductionmentioning
confidence: 99%